Some nitroimidazole derivatives as antibacterial and antifungal agents in in vitro study - Żwawiak, Justyna; Olender, Dorota; Zaprutko, Lucjusz (Journal of Medical Science, 2019)
Nitroimidazoles have wide range of therapeutic uses mainly as anaerobic antibacterials and antiprotozoal agents. Some bicyclic nitroimidazodihydrooxazoles and nitroimidazotetrahydrooxazines are found to be antituberculosis agents. Hence, the biological and chemical properties of mentioned substances are of great interest to scientists. The aim of this review is to show the general knowledge concerning the chemistry and biological activity of some nitroimidazole derivatives, based on experimental studies. The results of biological tests provide many useful information on the effects of particular groups or other structural elements on the level of pharmacological activity. Also, these studies can be helpful in further planning of syntheses of active substances with using nitroimidazole moiety.